2020
DOI: 10.3390/vaccines8030399
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy Evaluation of Recombinant Marek’s Disease Virus with REV-LTR

Abstract: Recently, chickens vaccinated with the CVI988/Rispens vaccine showed increased tumor incidence. Moreover, many strains of Marek’s disease virus (MDV) that were naturally integrated with the long terminal repeat (LTR) of the avian reticuloendotheliosis virus (REV) have been isolated, which means it is necessary to develop a new vaccine. In this study, two LTR sequences were inserted into Rispens to construct a recombinant MDV (rMDV). Then, the safety and efficacy of rMDV were evaluated separately in chickens. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The field farms included in the present study included vaccination with the bivalent vaccine comprising HVT and Rispens, which offer greater protection compared to HVT alone. Several researchers [ 18 - 20 ] have reported the effectiveness of the Rispens vaccine in protecting against tumors. However, in the present study, severe tumors were observed in the flocks vaccinated with the Rispens valence.…”
Section: Discussionmentioning
confidence: 99%
“…The field farms included in the present study included vaccination with the bivalent vaccine comprising HVT and Rispens, which offer greater protection compared to HVT alone. Several researchers [ 18 - 20 ] have reported the effectiveness of the Rispens vaccine in protecting against tumors. However, in the present study, severe tumors were observed in the flocks vaccinated with the Rispens valence.…”
Section: Discussionmentioning
confidence: 99%
“…Infections in stock and cattle increase the risk of starvation; thus, vaccination programs in animals have been encouraged. For such purpose, Song et al [ 11 ] demonstrated that recombinant Marek’s disease virus (rMDV) with reticuloendotheliosis virus (REV)-LTR (long terminal repeat) shows a good safety profile in target chickens and environment and can be used in the development of a vaccine against MDV. An interesting program, as discussed by Antenucci et al, used outer membrane vesicles to immunize chickens against Gallibacterium anatis , which was proven both effective and economically advantageous [ 12 ].…”
mentioning
confidence: 99%